Engineering Lipases: walking the fine line between activity and stability. (27th November 2017) - Dasetty, Siva; Blenner, Mark A; Sarupria, Sapna
Abstract: Lipases are enzymes that hydrolyze lipids and have several industrial applications. There is a tremendous effort in engineering the activity, specificity and stability of lipases to render them functional in a variety of environmental conditions. In this review, we discuss the recent experimental and simulation studies focused on engineering lipases. Experimentally, mutagenesis studies have demonstrated that the activity, stability, and specificity of lipases can be modulated by mutations. It has been particularly challenging however, to elucidate the underlying mechanisms through which these mutations affect the lipase properties. We summarize results from experiments and molecular simulations highlighting the emerging picture to this end. We end the review with suggestions for future research which underscores the delicate balance of various facets in the lipase that affect their activity and stability necessitating the consideration of the enzyme as a network of interactions.